Idiomatic Expressions in One Piece Live Action Film Dialogue: A Pedagogical Perspective - Ramadhani, Dhea (Indonesian Journal of Educational Science (IJES), 2024)
This research aims to find out the types of idiomatic expressions based on their meanings and to analyse the educational values contained in the One Piece Live Action movie. The data of this research are idiomatic expressions taken from the movie One Piece Live Action and analysed using the theory of types of idiomatic expressions by Fernando and the theory of educational value by Zubaedi. This research uses a qualitative approach with a qualitative descriptive design and a notetaking approach as a data collection procedure. The results of this study show that there are 86 idiomatic expressions in the film. These include 16 pure idioms, 64 semi-literal idioms, and 6 literal idioms. In addition, there are several educational values contained in the idiomatic expressions, such as honesty, discipline, hard work, curiosity, national spirit, respect for achievement, friendship, social care, and responsibility. In conclusion, the One Piece live-action movie not only presents interesting dialogues but also teaches important values through the use of idioms.